φ Meson in nuclear matter and nuclei - Cobos-Martínez, J. J.; Tsushima, K.; Krein, G. [UNESP]; Thomas, A. W. (My University, 2017)
The mass and decay width of the φ meson in cold nuclear matter are computed in an effective Lagrangian approach, with the medium dependence of these properties obtained by evaluating kaon-antikaon loop contributions to the φ self-energy. At normal nuclear matter density, we find a downward shift of the φ mass by a few percent, while the decay width is enhanced by an order of magnitude. We also present φ–nucleus bound state energies and absorption widths for some selected nuclei, using complex optical potentials obtained in the local density approximation. Our results suggest that the φ should form bound states with all the nuclei considered. However, the identification of the signal for these predicted bound states will need careful investigation because of their sizable absorption widths.